PROSEDUR PENANGANAN KREDIT BERMASALAH PADA PT.BPR SERANG (PERSERODA) CABANG KASEMEN - Dabella Yunia; Kurniasih Dwi Astuti; Rika Destri Wulansari (RISTANSI: Riset Akuntansi, 2022)
A bank will not be separated from the problem of non-performing loans. The non-performing loans have a negative impact on both parties, namely for the bank and also for the debtor. The pliers method used in this study is a descriptive method. Researchers convey research results from direct observations in the field. The results of the observations show that the factors that cause non-performing loans at PT BPR Serang (Perseroda) Kasemen Branch are in the form of internal factors from the bank, internal factors from the debtor, and also external factors that are beyond expectations. Efforts to rescue non-performing loans (NPL) are in the form of rescheduling, re-conditioning, and realignment. During the COVID-19 pandemic, PT BPR Serang (Perseroda) Kasemen Branch carried out credit rescue by using the credit restructuring method, which was in accordance with OJK regulations regarding the stimulus for the impact of the spread of the COVID-19 virus for affected communities.